Shrub anti-herbivore defenses exhibit non-linear and varied responses to increased herbivore density - Justin P. Young; Timothy E. Fulbright; Charles A. DeYoung; David G. Hewitt; David B. Wester; Don A. Draeger (Basic and Applied Ecology)
Plants may produce induced defenses such as longer thorns or secondary compounds to cope with higher levels of herbivory. However, it is unclear if physical and chemical plant defenses increase incrementally along a gradient of herbivore densities. We hypothesized that physical and chemical anti-herbivore defenses in selected shrubs increase with increasing herbivore density. We tested our hypothesis using four 0.81 km2 paddocks on each of two ranches in southern Texas, USA, that were fenced to exclude ingress and egress by white-tailed deer (Odocoileus virginianus). Target densities of deer on each ranch were 0 (control), 25, 49, and 74 deer/km2. Pelleted feed was provided ad libitum in each paddock. In July 2014, we selected ten plants of blackbrush acacia (Vachellia rigidula), twisted acacia (Vachellia schaffneri), and spiny hackberry (Celtis ehrenbergiana) in each of the four research paddocks on each ranch. We marked stems on each plant and recorded length of the main stem, lateral stems, and thorns during July 2014–2016. We collected leaf and stem samples from 20 plants of each of the three browse species during July and October 2014 and 2015 for analysis of crude protein and tannins. Branch density of blackbrush acacia was 38 % (25 deer/km2) to 123 % (49 deer/km2) greater in deer density treatments and thorn density of blackbrush acacia was 27 % greater in treatments with 74 deer/km2 than in control treatments. Spiny hackberry branch density was 2.5 times greater in treatments with 49 deer/km2 than in control treatments. Induction of plant antiherbivore defenses with increasing deer density occurred primarily in blackbrush acacia. A key finding is that induced physical and chemical defenses in shrubs can respond to increasing herbivore density in a non-linear fashion and the combination of defense strategies can vary depending on herbivore density.